Pengaruh Konflik Peran terhadap Kinerja Pegawai dengan Kecerdasan Spiritual sebagai Mediasi (Studi Kasus pada Pegawai Puskesmas Kota XYZ) - Dyana Yuri Aurora; Rahmi Fahmy (Universitas Samudra, 2020)
This study aims to analyze the effect of role conflict on employee performance; spiritual intelligence on role conflict; spiritual intelligence on employee performance; and, role conflict mediated by spiritual intelligence on employee performance. Role conflicts include intrarole conflict, intrasender conflict, interrole conflict, and conflicting expectations and requests and incompatible evaluation standards. 108 ASN employees working in four health centers in XYZ city were selected as samples using a purposive sampling method. The results of the study found that conflict of intrasender and conflicting expectations and requests and incompatible evaluation standards had a significant effect on employee performance; and that spiritual intelligence partially mediates the relationship between conflicting expectations and expectations and incompatible evaluation standards on employee performance. Dominant factor that affect employee performance is conflicting expectations and requests and incompatible evaluation standards, so this factor should be a major concern for research objects in realizing their organizational goals.